2013
DOI: 10.1095/biolreprod.112.107110
|View full text |Cite
|
Sign up to set email alerts
|

t-SNARE Syntaxin2 (STX2) Is Implicated in Intracellular Transport of Sulfoglycolipids During Meiotic Prophase in Mouse Spermatogenesis

Abstract: Syntaxin2 (STX2), also known as epimorphin, is a member of the SNARE family of proteins, with expression in various types of cells. We previously identified an ENU-induced mutation, repro34, in the mouse Stx2 gene. The Stx2(repro34) mutation causes male-restricted infertility due to syncytial multinucleation of spermatogenic cells during meiotic prophase. A similar phenotype is also observed in mice with targeted inactivation of Stx2, as well as in mice lacking enzymes involved in sulfoglycolipid synthesis. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 53 publications
3
28
0
Order By: Relevance
“…In some experiments, after isolation of specifically staged seminiferous tubules, a squash method was used for the cytological preparation. Squash preparations of germ cells were prepared based on previously described methods (Fujiwara, et al 2013; Kotaja, et al 2004), with some modifications. Briefly, mouse testes were placed in PBS and detunicated.…”
Section: Methodsmentioning
confidence: 99%
“…In some experiments, after isolation of specifically staged seminiferous tubules, a squash method was used for the cytological preparation. Squash preparations of germ cells were prepared based on previously described methods (Fujiwara, et al 2013; Kotaja, et al 2004), with some modifications. Briefly, mouse testes were placed in PBS and detunicated.…”
Section: Methodsmentioning
confidence: 99%
“…Sections (5 m) were stained with hematoxylin and eosin (HE) for evaluation of spermatogenesis. Immunohistochemistry was performed as previously described (Fujiwara et al 2013). Mouse monoclonal anti-human PCNA primary antibody and anti-rat IgG HRP labeled secondary antibody (Table 1) were used to label the histological sections.…”
Section: Methodsmentioning
confidence: 99%
“…In 2013, Fujiwara et al. () demonstrated that nullizygosity of Stx2 results in universal maturation arrest in mice. Stx2 mutant mice characteristically exhibit spermatogenic failure with multinucleated spermatocytes.…”
mentioning
confidence: 99%
“…Stx2 mutant mice characteristically exhibit spermatogenic failure with multinucleated spermatocytes. STX2 (MIM# 132350, NM_001980.4) encodes a transporter for sulfoglycolipids, which are indispensable in the maintaining of intercellular bridges of developing spermatocytes (Fujiwara et al., ). To date, however, STX2 mutations have not been identified in humans.…”
mentioning
confidence: 99%
See 1 more Smart Citation